2004
DOI: 10.1016/j.curtheres.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of benzydamine hydrochloride and Salvia officinalis as an adjuvant local treatment to systemic nonsteroidal anti-inflammatory drug in controlling pain after tonsillectomy, adenoidectomy, or both: an open-label, single-blind, randomized clinical trial

Abstract: Background: Benzydamine hydrochloride (BNZD) is a nonsteroidal antiinflammatory drug (NSAID) used in an oral rinse formulation as an adjuvant to other NSAIDs in controlling postoperative pain after tonsillectomy, adenoidectomy, or both. Salvia officinalis (SO) is a topically applied herbal preparation frequently used for the same indication. Pain, bleeding, and infection are the most common postoperative complications of tonsillectomy.Objective: The aim of this study was to compare the efficacy and tolerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In this study, the high ratio of emergence agitation accompanied with high visual analog scale (VAS), the ratio of emergence agitation decreased when levels of postoperative pain was restrained, which verified that levels of postoperative pain in young children are associated with more emergence agitation. This finding supports the notion that inadequate postoperative pain control and sedation may have contributed to the large differences in emergence agitation noted in other studies [3,4,30,31]. The incident of EA was also decrease with the deepen of sedation, which means the incident of EA is correlated to the degree of sedation, this is in accordance with other researches' results [32][33][34].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In this study, the high ratio of emergence agitation accompanied with high visual analog scale (VAS), the ratio of emergence agitation decreased when levels of postoperative pain was restrained, which verified that levels of postoperative pain in young children are associated with more emergence agitation. This finding supports the notion that inadequate postoperative pain control and sedation may have contributed to the large differences in emergence agitation noted in other studies [3,4,30,31]. The incident of EA was also decrease with the deepen of sedation, which means the incident of EA is correlated to the degree of sedation, this is in accordance with other researches' results [32][33][34].…”
Section: Discussionsupporting
confidence: 95%
“…Several studies indicate that pain treatment after tonsillectomy has been inadequate [1][2][3][4]30,31]. Up to recent years opioids are widely used analgesics for peri-and postoperative pain in children.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia, one of main pharmacological properties of dexmedetomidine, is deemed to play an important role in preventing EA after inhalation anesthesia. Some studies found that although the pain alone could not cause EA [ 58 , 59 ], inadequate postoperative pain control may be closely associated with varying differences in the incidence of EA[ 60 , 61 ], therefore it is one of major causes of the increased frequency and severity of EA[ 6 , 62 ]. For children, it is too difficult to describe pain objectively, therefore various pain assessment tools such as the visual analogue scale (VAS) [ 63 ] and the objective pain scale (OPS) [ 64 ] were to compare the number of patients who needed post-anesthesia pain control.…”
Section: Discussionmentioning
confidence: 99%
“…72 However, this effect of S. officinalis is not more powerful than the benzydamine hydrochloride in controlling postoperative pain after tonsillectomy or adenoidectomy. 73 …”
Section: Pharmacological Activitiesmentioning
confidence: 99%